Fate and Effects of Oil Pollutants in Extremely Cold Marine Environments. - Atlas,Ronald M. (1974)
The biodegradability of different crude oils depended on their composition and temperature. Heavier oils were more resistant to biodegradation, but lighter oils, while more susceptible to degradation at warm temperatures, contained volatile components that inhibited crude oil mineralization at reduced temperatures. It was possible to stimulate degradation of Prudhoe crude oil by fertilization and microbial seeding. Success of stimulated biodegradation depended on providing sufficient nutrients for extensive microbial metabolism in an oleophilic form and on the presence of appropriate oil degrading microorganisms for the given ecosystem. Microbial degradation did not increase toxicity to invertebrate test organisms. Amphipods were only killed by direct physical contact with oil slicks. The seed Pseudomonas sp. was not pathogenic or toxic to the bioassay organisms. Petroleum was found to inhibit microbial photosynthesis and nitrogen fixation, but not respiration. Chronically polluted areas had abnormally high numbers of fungi and low numbers of bacteria. Pristine Alaskan waters all contained microorganisms capable of oil biodegradation.